2022
DOI: 10.1039/d0cs01599g
|View full text |Cite
|
Sign up to set email alerts
|

Tailored design of nanofiltration membranes for water treatment based on synthesis–property–performance relationships

Abstract: This review article is devoted to bridging the conventional and newly-developed NF membranes with the potential environmental applications by systematically discussing the synthesis–property–performance relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
111
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(111 citation statements)
references
References 406 publications
0
111
0
Order By: Relevance
“…For the PSf substrates with pore size of 30–70 nm, RMS roughness of 5–10 nm and water contact angle of 60–80°, it is found that more permeable, hydrophilic supports produced low permeability TFC membranes, whereas highly porous, relatively hydrophobic supports produced more permeable TFC membranes 25 . But other researchers conclude that a smooth, hydrophilic, and tough substrate membrane with uniform pore size is a better choice for TFC preparation 27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the PSf substrates with pore size of 30–70 nm, RMS roughness of 5–10 nm and water contact angle of 60–80°, it is found that more permeable, hydrophilic supports produced low permeability TFC membranes, whereas highly porous, relatively hydrophobic supports produced more permeable TFC membranes 25 . But other researchers conclude that a smooth, hydrophilic, and tough substrate membrane with uniform pore size is a better choice for TFC preparation 27 …”
Section: Introductionmentioning
confidence: 99%
“…25 But other researchers conclude that a smooth, hydrophilic, and tough substrate membrane with uniform pore size is a better choice for TFC preparation. 27 The present reports mainly focus on the substrate surface properties, and mostly use PSf membranes. The results may be only applicable for certain conditions, such as certain material, pore size, and hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…10 NF membranes, on the other hand, work on the combination of hydrodynamic filtration, the solution-diffusion mechanism and the Donnan exclusion principle. 188,189 Upon incorporation of nanochannels into the membrane matrix, molecular sieving, interface effects and solution-diffusion mechanisms are probable mechanisms that govern the separation of water and solutes. For transport through the nanochannel, surface friction as well as the interactions between the channel cavity and permeation species will affect the transport rates of the permeating species (this will be elaborated in the subsequent subsections).…”
Section: Separation Mechanismsmentioning
confidence: 99%
“…Membrane, one of the most typical 2D materials, has emerged as a well-liked choice for reclaiming clean water from wastewater for reuse. 110 According to the intrinsic property and separation principle, membrane generally can be classified into several types, including microfiltration (MF, 0.1-5 mm), ultrafiltration (UF, 0.5-100 nm), nanofiltration (NF, 0.5-10 nm) and reverse osmosis (RO, o0.5 nm), etc., which can achieve the interception of suspended particles, organic molecules, colloidal haze, oil emulsions, proteins, bacteria, viruses, even ions from raw water. 99,111 Excitingly, natural polyphenols have been extensively used as coating of the membrane via surface chemistry strategy to realize the desirable functionality.…”
Section: Membranesmentioning
confidence: 99%